Der internationale Schutz der Privatsphäre vor geheimdienstlicher Überwachung Die geheimdienstliche Ausspähung der Telekommunikation von Individuen im Lichte des IPpbR und der EMRK - Golghalyani, Sahra (Universitätsverlag Göttingen, 2022)
This dissertation examines intelligence surveillance of private telecommunications and its compatibility with the international human right to privacy in Art. 17 ICCPR and in Art. 8 ECHR. These articles provide comprehensive protection against the most modern forms of surveillance including bulk interception. Several criteria apply in terms of the foreseeability of the surveillance laws. Telecommunication's interception should be subject to authorisation and supervision by independent authorities and effective remedies should be available. Moreover, the study analyzes the extent to which the surveilling state and the state of residence violate their human rights obligations in cases of cross-border surveillance. The main question is whether the established definitions of "jurisdiction" are applicable to this extraterritorial scenario. The extraterritorial exercise of jurisdiction can also be based on effective control over specific objects relevant to human rights. According to this approach, telecommunications data are objects relevant to individual's right to correspondence and data protection.